THE ABUNDANCE AND POTENTIAL REGENERATION OF SURILI (PRESBYTIS COMATA) NATURAL FEED VEGETATION IN THE PALUTUNGAN FOREST ZONE OF GUNUNG CIREMAI NATIONAL PARK, WEST JAVA - Anggreyni D Br Simamora, Ruth
Surili is an endangered primate whose life depends on forest vegetation. Gunung Ciremai National Park (TNGC) is one of the ideal forest areas as a surili habitat. Problems that have an impact on the surili population in the area, namely the transfer of functions and land degradation as well as surili conflicts with the community. This is suspected to cause a decrease in the quantity of surili natural food so preservation must be carried out. This study aims to obtain information on the abundance and regeneration potential of surili natural feed vegetation in the Core Zone of the Palutungan TNGC. Vegetation analysis is carried out using a combination of the method of squared plots and path plots. 25 types of vegetation constituents of surili habitat in the area with a high evenness index (E>0.6) were obtained. The abundance of surili feed vegetation by density and INP is included in the good criteria since the proportion of feed vegetation is much higher than that of non-feed vegetation (4:1), with the percentage of feed vegetation ±80% and non-feed vegetation ±20%. There are 5 types of feed vegetation with the highest INP, namely kuray (61.57%), mersawa (55.50%), kipare (48.92%), saninten (40.09%), and mara (29.85%). Based on the regeneration status of each type, the regeneration potential of surili feed vegetation, namely saninten has a good regeneration status, mersawa and kipare have fair regeneration status, mara, puspa, and are famous for having a poor regeneration status, and kurai has a status of not regenerating.